UZBEKISTAN – SAUDI ARABIA RELATIONS: A NEW STAGE OF COOPERATION - Muhammadolim Muhammadsiddiqov (International Scientific and Current Research Conferences, 2024)
This article explores the evolving diplomatic, economic, cultural, and strategic relations between the Republic of Uzbekistan and the Kingdom of Saudi Arabia over the past three decades. It examines key milestones in bilateral cooperation, including high-level visits, signed agreements, and multilateral initiatives such as the Central Asia–Gulf Cooperation Council summits. Special emphasis is placed on the alignment of national development strategies—“Uzbekistan–2030” and “Vision 2030”—as a foundation for expanding collaboration in energy, technology, education, and religious tourism. The study argues that the current trajectory of Saudi–Uzbek relations reflects a deepening of mutual interests rooted in long-term regional stability, strategic integration, and shared cultural values. The article concludes that this partnership is poised to contribute significantly to geopolitical balance, economic modernization, and interregional connectivity in both Central Asia and the Gulf.